Sonoelastographic evaluation of the masseter muscle before and after mandibular setback surgery - Etoz, M.; Demirbas, A. E.; Topsakal, K. G.; Etoz, O. A.; Kaya, M. O.; Alkan, A. (Wolters Kluwer Medknow Publications, 2020)
Aims: The purpose of this study is to compare the thickness and elasticity of the masseter muscle before and after orthognathic surgery in patients with class III skeletal deformity and to investigate the relationship between the sonographic changes in the masseter muscle and the amount of mandibular setback. Subjects and Methods: The study group consisted of 14 patients with skeletal class III malocclusions who had orthognathic surgery. The control group consisted of 14 patients who had dental and skeletal class I occlusion. Muscle thickness measurements were performed with B-mode and high-frequency linear scanning probe of the ultrasound device. Elastography feature and muscle hardness ratio were obtained by applying compression and decompression on muscles at rest and during maximum contraction in the transverse plane. Patients were categorized into two groups according to the mandibular setback as <5 mm and >= 5 mm. Results: The masseter muscle thickness after surgery was found statistically increased bilaterally in both at rest and during contraction for the study group (P < 0.05). No difference was found between preoperative orthognathic measurements and postoperative measurements for elasticity index ratio measurements (P > 0.05). Conclusion: We believe that in the present study important findings have been emphasized for further research aiming to investigate the possible relationship between masticatory alterations and surgical outcomes after orthognathic surgery.
Keywords: Elastography; mandibular setback; masseter muscle; orthognathic surgery; ultrasonography